Pilihan raya dan pembangunan politik Sarawak - Ahmad Nidzammuddin Sulaiman; Zaini Othman; Universiti Malaysia Sabah (Kota Kinabalu, Sabah : Universiti Malaysia Sabah, 2009)
Essays on state elections and political conditions in Sarawak, Malaysia.
Includes bibliographical references : (p. [215]-222) and index.
In Malay.
Keywords: Elections -- Malaysia -- Sarawak; Sarawak -- Politics and government